The nomenclatural status of the two “spiny-wristed” fiddler crabs: Uca spinicarpa Rathbun, 1900, and U. hesperiae Crane, 1975 (Crustacea: Brachyura: Ocypodidae) - Rosenberg, Michael S. (Zootaxa, 2013)
A secondary homonymy is documented for Gelasimus [= Uca] tetragonon var. spinicarpa Kossmann, 1877 (a species from the Red Sea), and Uca spinicarpa Rathbun, 1900 (a species from the Gulf of Mexico). Although Kossmann’s usage of the nomen spinicarpa has chronological priority, a reversal of precedence is required by Article 23.9 of the Code since Kossmann’s use has not been applied as a valid name since the original publication in 1877, while Rathbun’s use of the name has been applied over 50 times in the last half century. The species Kossmann was most likely referring to is today known as Uca hesperiae Crane, 1975, a name which may be retained in light of the reversal of precedence.